Comment (re)connaître et traduire la signification des mots d ’une langue étrangère - Florczak, Jacek (Wydawnictwo Naukowe UAM, 2001)
Assuming that a profound knowledge of a second language is impossible without the knowledge about the language itself, the author’s aim is to present the classical linguistic methods of meaning analysis as helpful tools in the formation and development of second language semantic competence at the advanced and intermediate levels. These methods operate on one language and decompose a word’s meaning into relevant and discrete features. They vary from the logical analysis of features common to all referents denoted by a word, through the semic analysis of words compared in semantic fields, to the componential analysis which determines the range of a word’s use in context. While all these analyses concern the semantic norm, the discursive content is the object of research of the interpretative analysis and translation, where the realization of meaning in discourse is always a function of semantic norm and where the lack of knowledge of the normative content leads directly to faulty or strange translations.
How to recognize and translate the meaning of foreign language words?